Attitudes of Italian mental health nurses towards mental illness and recovery: a cross-sectional study - Giovanni Napoli; Simone Autuori; Kumi Senkyire Ephraim (AIMS Press, 2023)
Background: Mental health nurses' (MHNs) stigma and discrimination against people with mental illnesses are obstacles to recovery and the development of effective care and treatment. Although many authors have been interested in exploring stigma among general health professionals, paradoxically, less and non-generalizable evidence is available on this phenomenon among MHNs. Understanding the factors associated with stigma and its relationship to recovery attitudes among MHNs could allow for more accurate interventions and improve patient care outcomes. Objective: This study conducted on a sample of Italian psychiatric nurses had the objective of analyzing the aptitude for recovery and the tendency towards stigma of these professionals towards mental illness. Methodology: A cross-sectional web survey was conducted on a sample of Italian MHNs, who were administered two validated tools, the RAQ-7 (assessment of recovery aptitude) and the WHO-HC-15 (assessment of stigma) respectively. Results: A total of 204 MHNs were interviewed. The analysis showed positive overall scores (high recovery aptitude and low stigma levels) among participating MHNs. The attitude to recovery appeared to be directly related to a lower tendency to stigma towards mental illness. It has been observed that MHNs with advanced levels of education appear to be more predisposed to recovery, as well as generally less stigmatizing. There is evidence that the setting in which care is provided, marital status and age can play a significant role in the tendency to stigmatization. Conclusion: Our manuscript could assist nursing executives, leaders or educators in making decisions about managing and preventing stigma among MHNs.